Contingence et représentation arborescente : le cheminement de Darwin des les otebooks jusqu’à la première édition de l’Origine des Espèces - Soubbotnik, Michael A. (Studia Romanica Posnaniensia, 2018)
This study attempts to show how Darwin’s 1otebooks provide evidence that the author of the Origin of the Species moved further and further away from various versions of a “system of nature” based on some complex, abstract, finalized order, by combining empirical testing and shifts in the schematic representation of the relations between taxonomic categories.